Hubungan antara sanitasi dengan kejadian stunting pada balita di Kabupaten Bolaang Mangondow Timur - Lumente, Kalista; Bolang, Alexander; Kapantow, Nova (UNIVERSITAS SAM RATULANGI, 2024)
Background: Toddlers are an age group that is susceptible to malnutrition which, in the long term, can lead to stunting if not adequately addressed. Stunting is a condition in which a child is significantly shorter than the normative height for their age, specifically measured as a length or height index that falls below -2 standard deviation (SD). Infectious diseases due to improper sanitation are one of the factors that lead to stunting. According to the SSGI (Indonesian Nutrition Status Study) 2021 report, East Bolaang Mongondow Regency is the district with the highest prevalence of stunting in North Sulawesi. Aim : To determine the association of sanitation to stunting incidence in toddlers in East Bolaang Mongondow Regency. Methods: This is an analytical survey research using secondary data, analysed using a Fisher's exact test statistical test. Results: The analysis showed the association between sanitation and stunting incidence of 71 toddlers aged over 24-59 months in East Bolaang Mongondow Regency were p=0.130. Conclusion: There was no meaningful relation between sanitation and stunting incidence in toddlers in East Bolaang Mongondow Regency. Keywords: sanitation, stunting, toddlers